2016
DOI: 10.1302/0301-620x.98b11.37526
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of necrotising fasciitis in diabetics and non-diabetics

Abstract: The LRINEC score must be used with caution in diagnosing necrotising fasciitis in diabetic patients. A high index of suspicion is key to the early diagnosis and subsequent management of these patients. Cite this article: Bone Joint J 2016;98-B:1563-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 32 publications
7
61
1
Order By: Relevance
“…Pain is induced in the infarctional nerve-dominated skin area. With NF, https://doi.org/10.22467/jwmr.2019.00598 the overlying skin is accompanied by redness, vesicles, bullae, necrosis, or crepitus [6].…”
Section: Discussionmentioning
confidence: 99%
“…Pain is induced in the infarctional nerve-dominated skin area. With NF, https://doi.org/10.22467/jwmr.2019.00598 the overlying skin is accompanied by redness, vesicles, bullae, necrosis, or crepitus [6].…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Diabetes mellitus is the most prevalent risk factor and is present in up to 71% of infections. [6][7][8][9][10][11] Intravenous drug abuse is another common predisposing factor in as many as 43% of patients with NSTI. 11 Other associations include smoking, trauma, prior methicillinresistant Staphylococcus aureus (MRSA) infection, chronic hepatitis C, HIV/AIDS, chronic illness, increasing age, NSAID use, and exposure to persons infected with invasive group A Streptococcus.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Although this Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score has not been validated in a prospective trial, the components of the score are still useful in addition to the overall assessment and as a prognostic tool. 9,19,28 A study retrospectively comparing a cohort of patients with severe erysipelas subsequently diagnosed with either cellulitis or NSTI found that the overall clinical presentation for each was similar; however, NSTI patients were more likely to have higher pain scores, a higher CRP level, and a higher LRINEC score 29 (Table 2). Another series analyzing vibrio NSTI found severe hypoalbuminemia, thrombocytopenia, and bandemia as a predictor of mortality and suggested that these values be used to direct early surgical intervention.…”
Section: Laboratory Evaluationmentioning
confidence: 99%
“…Diabetes is associated with an increased risk of infections 4,17,18 and is overrepresented among patients with NSTI, with a reported frequency of 20%-70%. 10,11,15,[19][20][21][22][23] In contrast, the World Health Organization (WHO) estimates global diabetes prevalence to be 8.5% in adults. 24 Concomitant diabetes seems to be a negative prognostic factor among patients with NSTI with increased risk of death, amputation, and infectious complications.…”
Section: Necrotizing Soft Tissue Infectionsmentioning
confidence: 99%
“…24 Concomitant diabetes seems to be a negative prognostic factor among patients with NSTI with increased risk of death, amputation, and infectious complications. 22,23,[25][26][27] Hyperglycemia could be a factor associated with outcome in diabetic patients with NSTI. 26…”
Section: Necrotizing Soft Tissue Infectionsmentioning
confidence: 99%